Convergence and Divergence in Emerging Donor Finance: A Comparative Analysis of Chinese and Indian Exim Banks in Ethiopia - Zhengli Huang; Pritish Behuria (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Zhengli Huang and Pritish Behuria examine projects financed by Indian and Chinese Exim Banks to analyze how the development financing of two 'emerging' donors – India and China – has evolved in Ethiopia. In India and China, Exim Banks work both as export credit agencies and other traditional development finance organizations, thereby blurring the boundary between development assistance and economic cooperation. The authors selected Ethiopia as it is a strategic partner for both countries, and existing literature has shown that the Ethiopian government is an outlier on the continent in employing its diplomatic relations to support strategic developmental goals.
Keywords: 330